2021
DOI: 10.2340/00015555-3890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Lockdown on Tumour Burden of Melanoma and Cutaneous Squamous Cell Carcinoma

Abstract: There is little evidence regarding the impact of COVID-19 lockdown on skin tumour burden. The COVID-19 lockdown resulted in a reduction in surgery for melanoma and cutaneous squamous cell carcinoma and an increase in the proportion of tumours with a worse prognosis. The increase was due to patient-dependent factors; in particular, fear of SARS-CoV-2 infection. Therefore, health education programmes targeting the general population are needed to ensure the prompt treatment of patients with skin cancer. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 13 publications
2
34
1
2
Order By: Relevance
“…Interestingly, melanoma thickness and the percentage of thick melanomas observed in our study both before and during the pandemic were higher than the ones reported by studies conducted in other countries [ 8 , 9 , 14 ]. Higher rates of advanced tumors and a lower survival were already reported in Central and Eastern Europe in previous studies [ 25 ]. Differences in the general educational status, reduced government expenditure on education and a lack of specific health education, resulting in a lower awareness among the general population and physicians, may at least partly explain the later diagnosis of advanced stages in our study.…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly, melanoma thickness and the percentage of thick melanomas observed in our study both before and during the pandemic were higher than the ones reported by studies conducted in other countries [ 8 , 9 , 14 ]. Higher rates of advanced tumors and a lower survival were already reported in Central and Eastern Europe in previous studies [ 25 ]. Differences in the general educational status, reduced government expenditure on education and a lack of specific health education, resulting in a lower awareness among the general population and physicians, may at least partly explain the later diagnosis of advanced stages in our study.…”
Section: Discussionmentioning
confidence: 65%
“…Reductions of new melanoma and/or cSCC diagnoses have also been observed in Spain 5 and Chile 6 . A large Canadian study showed a reduction of most cases of cancer during the COVID‐19 pandemic especially for melanoma and cervical, endocrinological and prostate cancers 7 .…”
Section: Figurementioning
confidence: 92%
“…Although reporting of skin cancer has fortunately increased again, the rebound is thought to be incomplete, but most data still require additional adjustment for changed population age distributions. [3][4][5][6][7][8][9] These nationwide reductions in skin cancer incidence offer a unique possibility to study the impact of diagnostic delay on skin cancer characteristics. Researchers have hypothesized that the delay of skin cancer diagnoses may have resulted in cases of skin cancer progressing to unfavourable cancer stages.…”
mentioning
confidence: 99%